Traumatic perforation: determinants of conductive hearing loss - S., Ravi K.; N., Ravishankar S. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Traumatic perforations of the tympanic membrane are very common in day to day life and it may be due to direct or indirect source. The aim of this study is to evaluate the various factors which determine the degree of hearing loss in patients with traumatic perforation of tympanic membrane. Methods: A retrospective review was performed in 50 patients seen at the ENT department in our rural tertiary center over a period of two years between January 2015 to December 2016. The patients with history of ear trauma from various causes and with absolutely no previous history of any ear disease were included in our study. The data retrieved included parameters such as age, sex, side, cause of injury and presenting complaints such as hearing loss, earache, tinnitus, and vertigo. A detailed clinical and otoscopic examination was done to determine the size and location of the perforation. Hearing was assessed using pure tone audiometry (PTA) to determine the degree of hearing loss and to correlate with frequency, size and location of perforation. Results: A total of 50 patients with traumatic perforations of the tympanic membrane were enrolled for the study, comprising of 32 males and 18 females patients. Age of the patients ranged from12 to 65 years of age. The results showed that the most common mode of trauma was RTA (46%). Audiometry shows that the larger the tympanic membrane perforation, the larger the air–bone gap. Hearing loss was highest at the lowest frequencies and generally decreased as the frequency increased. The results also showed that there was no difference in air bone gap with relation to location of perforation (anterior vs. posterior). Conclusions: The conductive hearing loss resulting from a tympanic membrane perforation is frequency dependent, with the largest losses occurring at the lowest sound frequencies, hearing loss increases as size of the perforation increases and no relation with location of perforation.